Land Use and Land Cover Dynamics and Their Driving Factors in the Ritung Khola Watershed, Myagdi District, Nepal - Thapa, Mahendra Singh; Sunar, Chirag (The Himalayan Geographers, 2025)
This study examines the Land Use and Land Cover (LULC) changes in the Ritung Khola watershed of Nepal’s Myagdi district over a 20-year period (2000–2020) using remote sensing (RS) and geographic information system (GIS) techniques. Landsat satellite images from 2000, 2010, and 2020 were analyzed through supervised classification, categorizing the landscape into five major classes: forest, agricultural land, water bodies, barren ground, and settlement. Field surveys and ground truthing were conducted to validate the classification accuracy and assess the drivers of change. The findings reveal distinct trends in LULC dynamics. From 2000 to 2010, forest cover, water bodies, and settlements decreased, while agricultural and barren lands expanded significantly. In contrast, between 2010 and 2020, forest areas, water bodies, and settlements increased, whereas agricultural and barren lands declined. These shifts were influenced by multiple factors, including population dynamics (growth and migration patterns), economic drivers (agricultural dependence, livelihood opportunities), and natural disasters (frequent floods and landslides altering landforms). The study highlights the complex interplay of human and natural factors shaping LULC changes in the sub-watershed. The findings provide critical insights for policymakers and land managers, emphasizing the need for sustainable land use planning, forest conservation, and disaster risk reduction strategies. Effective watershed management must balance ecological preservation with socio-economic development to ensure long-term sustainability. By integrating these insights into policy frameworks, stakeholders can enhance resilience, protect ecosystem services, and support local livelihoods in the Ritung Khola watershed and similar regions facing comparable challenges.